ANALYSIS OF RISK FACTORS FOR PREGNANT WOMEN INFECTED WITH MALARIA: Analisis Faktor Resiko Ibu Hamil Yang Terinfeksi Malaria - Rahmadhani, Wulan; Aprina, Hardianti; Chamroen, Pall; Soe, Than Kyaw (Jurnal Berkala Epidemiologi, 2025)
Background: Malaria is a disease caused by protozoa infection of the genus Plasmodium transmitted through the bite of infected female Anopheles mosquitos. Malaria infection in pregnancy is detrimental to both the mother and the fetus. Several efforts to prevent and eradicate malaria have been implemented, but many pregnant women are still infected with malaria. Purpose: To know the risk factors for pregnant women infected with malaria. Methods: This study used the literature review method by searching for articles analyzing risk factors for pregnant women infected with malaria. Articles were searched from two databases, namely PubMed and Google Scholar. The keywords used are "Pregnant Women" AND "Infected Malaria". The inclusion criteria (IC) in the article search were publication year: articles published in the last 5 years from 2018-2023 with the subject of pregnant women infected with malaria; the paper should be full text, with a Cross-sectional and case-control study. Results: This study involves 10 articles discussing the analysis of risk factors for pregnant women infected with malaria. Some studies revealed that the host, agent, and environment highly determine the spread of malaria. The spread of malaria occurs when those three components support each other. Risk factors for malaria are pregnant women's residence, wire netting installation on ventilation, and use of mosquito nets and repellent. Conclusion: Based on the reviewed articles, it can be concluded that pregnant women who do not use mosquito nets and whose residences are close to standing water and bushes have a greater risk of getting malaria.